2023
DOI: 10.3390/ijms24044115
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Organokine Regulation in Non-Diabetic Obese Subjects: Halfway to the Cardiometabolic Danger Zone

Abstract: Altered organokine expression contributes to increased cardiometabolic risk in obesity. Our aim was to evaluate the associations of serum afamin with glucose homeostasis, atherogenic dyslipidemia, and other adipokines in severe obesity to clarify the early metabolic alterations. 106 non-diabetic obese (NDO) subjects and 62 obese patients with type 2 diabetes matched for age, gender, and body mass index (BMI) were enrolled in this study. We compared their data with 49 healthy, lean controls. Serum afamin and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(46 reference statements)
2
2
0
Order By: Relevance
“…Atherogenic dyslipidemia—characterized by higher triglycerides, VLDL, large LDL, small-dense LDL levels, and a smaller mean LDL size, as well as shifting toward small-sized HDL subfractions in NDO and obese T2D patients compared to lean controls—has been described in previous studies, and these finding are in line with the literature data [ 12 , 13 ]. Only one previous study reported a positive correlation between the serum kallistatin level and triglyceride-rich lipoproteins, i.e., VLDL in T2D patients with diabetic nephropathy [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…Atherogenic dyslipidemia—characterized by higher triglycerides, VLDL, large LDL, small-dense LDL levels, and a smaller mean LDL size, as well as shifting toward small-sized HDL subfractions in NDO and obese T2D patients compared to lean controls—has been described in previous studies, and these finding are in line with the literature data [ 12 , 13 ]. Only one previous study reported a positive correlation between the serum kallistatin level and triglyceride-rich lipoproteins, i.e., VLDL in T2D patients with diabetic nephropathy [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…In a large-scale study, each 10 mg/dL increment in afamin levels resulted in a 19% increase in the number of MS components ( 12 ). Importantly, mean afamin concentration in GHU subjects was found comparable to that of reported in morbidly obese T2DM subjects (105.2 vs. 109.2 μg/mL) ( 20 ), which might reflect the severity of metabolic dysregulation in GHU patients. Higher BMI, WC, WHR and fat mass found in GHU subjects could theoretically explain the higher afamin concentrations, however, afamin correlated only with WC among these parameters in AGHD.…”
Section: Discussionsupporting
confidence: 69%
“…Lipoprotein subfractions were determined using the Lipoprint ® System (Quantimetrix Corporation, Redondo Beach, CA, USA) using LDL and HDL subfraction tests according to the instructions of the manufacturer as described previously [7]. The lipoprotein subfractions were distributed based on their size.…”
Section: Determination Of Lipoprotein Subfractionsmentioning
confidence: 99%
“…Nondiabetic obese (NDO) individuals can be characterized by metabolic disturbances, including atherogenic dyslipidemia and early changes in organokine expression, but their glucose metabolism is still within normal ranges. Therefore, NDO represents an intermediate status between healthy subjects and obese T2D patients with altered organokine patterns, chronic inflammation, and increased cardiovascular risk [5,7]. Despite a lack of clear definitions for classifying obesity subgroups [8], there are some promising markers that are useful in making basic differentiations between these phenotypes [5].…”
Section: Introductionmentioning
confidence: 99%